Basic surgical skills and techniques - Kumar Jain, Sudhir MS FRCS (Edinburgh) FACS FICS Professor (Jaypee Brothers Medical Publishers, 2013)
The second edition of Basic skill and techniques represents a major advance over its firts edition. This highly acclaimed book comprehensively covers the essentials of a bright surgial career. The book has been widely accepted due to its simple yet thoroungh presentation. The second edition to this book brings a welcome change in the form of improved readability, enhanced figures and additions of four new chapters that cover basic surgical procedures, instruments and latest advances in the field of surgery.